2012
DOI: 10.1155/2012/678107
|View full text |Cite
|
Sign up to set email alerts
|

A Review Focused on the Psychological Effectiveness of Tai Chi on Different Populations

Abstract: As a popular exercise form, Tai Chi (TC) has been investigated to determine its contributions to an active and healthy lifestyle. There are an increasing number of researchers who focus on exploring the potential physiological and psychological benefits of TC but only a few systematic reviews of these benefits to a variety of populations. The purpose of this paper is to comprehensively evaluate the reported psychological benefits associated with practicing TC. Although many investigators have reported possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 62 publications
2
29
0
3
Order By: Relevance
“…As mentioned earlier, in this phenomenological study, one researcher examined the psychological effects of a brief segment of Taekwondo exercise on college students [15], while other studies about the positive aspects of martial arts training suggest that Tai Chi, for instance, benefits physical [23] and psychological [24,25] health. Yet another study examined the effects of Karate and mindfulness training on the cognitive abilities of older adults [26]; however, a comparable study about the effects of similar interventions on the holistic health and well-being of undergraduate students may prove informative to the general knowledge base pertaining to the positive effects of Eastern martial arts on the experience of stress.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, in this phenomenological study, one researcher examined the psychological effects of a brief segment of Taekwondo exercise on college students [15], while other studies about the positive aspects of martial arts training suggest that Tai Chi, for instance, benefits physical [23] and psychological [24,25] health. Yet another study examined the effects of Karate and mindfulness training on the cognitive abilities of older adults [26]; however, a comparable study about the effects of similar interventions on the holistic health and well-being of undergraduate students may prove informative to the general knowledge base pertaining to the positive effects of Eastern martial arts on the experience of stress.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, walking is one of the most recommended exercises, and it has been shown to have positive effects on various biochemical markers, including those relating to oxidative stress [7–11]. Tai Chi is another modality of exercise that is broadly recommended for the elderly, particularly for preventing falls and psychological wellbeing [12, 13]. In addition, it has recently been observed that Tai Chi stimulates the endogenous antioxidant enzymes activity and decrease the oxidative stress in middle-aged adults and pre- and postmenopausal women [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…El tai chi como técnica china milenaria basada en una serie de ejercicios mentecuerpo, que combina gestos de artes marciales con movimientos meditativos, en posturas de danza entrelazadas, puede convertirse en una alternativa para el manejo del ES (Carrillo, Gómez-López, & Vicente, 2017;Jiménez, Meléndez, & Albers, 2012;Lee et al, 2012;Wang et al, 2014;Zhang, Layne, Lowder, & Liu, 2012).…”
Section: Estrés Psicológico Y Tai Chiunclassified